Correction: Full spectral XANES imaging using the Maia detector array as a new tool for the study of the alteration process of chrome yellow pigments in paintings by Vincent van Gogh. Issue 4 (25th April 2015) - Monico, Letizia; Janssens, Koen; Alfeld, Matthias; Cotte, Marine; Vanmeert, Frederik; Ryan, Chris G.; Falkenberg, Gerald; Howard, Daryl L.; Brunetti, Brunetto Giovanni; Miliani, Costanza
<x xml:space="preserve">Abstract</x> Correction for 'Full spectral XANES imaging using the Maia detector array as a new tool for the study of the alteration process of chrome yellow pigments in paintings by Vincent van Gogh' by Letizia Monico et al., J. Anal. At. Spectrom., 2015, DOI: 10.1039/c4ja00419a.